Case report: accelerated cathodal HD-tDCS over the right dorsolateral prefrontal cortex in hoarding disorder - Brunelin, Jerome; Neige, Cécilia; Eche, Julien; Galvao, Filipe; Bation, Rémy; Mondino, Marine (Frontiers in Human Neuroscience, 2024)
Hoarding disorder is an under-recognized condition characterized by the excessive acquisition of possessions and difficulty in disposing of them, which can have dramatic consequences. As hoarding disorder is difficult to treat and associated with high levels of disability in all areas of functioning, there appears to be a critical need to develop novel, tailored therapeutic strategies. Noninvasive brain stimulation techniques hold promise as potential therapeutic interventions for various psychiatric conditions and as a tool to modulate impulsivity when applied over the dorsolateral prefrontal cortex (DLPFC). Therefore, we hypothesized that delivering accelerated cathodal high-definition direct transcranial stimulation (HD-tDCS) over the right DLPFC could be a suitable approach to alleviate symptoms in patients with hoarding disorder. In a case report, we observed beneficial clinical effects on acquisition and depressive symptoms after 15 sessions of three daily 20-minute sessions. Accelerated cathodal HD-tDCS over the right DLPFC appears to be a safe and appropriate intervention for patients with hoarding disorder. However, randomized, sham-controlled trials are needed to further validate these encouraging findings.